Residents’ perceptionof Barão de Cocais (MG) about the creation of the Serra do Gandarela National Park and the impacts triggeredby the miningactivity (Research, Society and Development, 2018)
Mining activity is responsible for the raw materials supply that allows the maintenance of life, on the other hand, this activity triggers several impacts. Thus, this research aimed to analyze the residents’ perception of Barão de Cocais, MG, about the creation of the Serra do Gandarela National Park (PARNA)and about the mining activity impacts on the environment and society in general. The obtained data allowed to verify that the residents of the municipality in question was not aware of the creation of this PARNA. Beside this it was possible to notice a greater concern about the negative environmental impacts than the positive socioeconomic impacts, caused by the mining.